Contrast-enhanced magneto-photo-acoustic imaging in vivo using dual-contrast nanoparticles☆ - Qu, Min (Elsevier, 2014)
By mapping the distribution of targeted plasmonic nanoparticles (NPs), photoacoustic (PA) imaging offers the potential to detect the pathologies in the early stages. However, optical absorption of the endogenous chromophores in the background tissue significantly reduces the contrast resolution of photoacoustic imaging. Previously, we introduced MPA imaging – a synergistic combination of magneto-motive ultrasound (MMUS) and PA imaging, and demonstrated MPA contrast enhancement using cell culture studies. In the current study, contrast enhancement was investigated in vivo using the magneto-photo-acoustic (MPA) imaging augmented with dual-contrast nanoparticles. Liposomal nanoparticles (LNPs) possessing both optical absorption and magnetic properties were injected into a murine tumor model. First, photoacoustic signals were generated from both the endogenous absorbers in the tissue and the liposomal nanoparticles in the tumor. Then, given significant differences in magnetic properties of tissue and LNPs, the magnetic response of LNPs (i.e. MMUS signal) was utilized to suppress the unwanted PA signals from the background tissue thus improving the PA imaging contrast. In this study, we demonstrated the 3D MPA imaging of LNP-labeled xenografted tumor in a live animal. Compared to conventional PA imaging, the MPA imaging show significantly enhanced contrast between the nanoparticle-labeled tumor and the background tissue. Our results suggest the feasibility of MPA imaging for high contrast in vivo mapping of dual-contrast nanoparticles.